The Effect of Variation in the Proportion of Artificial and Natural Feed on Feed Selection and Consumption by Eel (Monopterus sp.) - Sintiya, Titik; Abidin, Zaenal; Muahiddah, Nuri (Aquaculture Department, University of Mataram, 2025)
Swamp eel is one of the fishery commodities favored by the community. Swamp eel cultivation activities have not been widely developed due to the lack of feed availability to support cultivation efforts. Instead of using artificial feed, the farmer has used natural feed in the form of earthworms so far. Therefore, in this study, artificial feed and natural feed are combined to stimulate the feed acceptance of the eel. This study determined the proportion between artificial and natural feed on the level of feed consumption of swamp eel. The method used consisted of four treatments: 50% feed + worms (control diet), 75% feed + 25 snails, 50% feed + 50% snails, and 25% feed + snails 75%. The results show that the differences in the proportion of artificial and natural feed did not affect the feed selection, time response, and feed consumption by eel. Therefore, 25% snails and 75% artificial feed are recommended to stimulate the eel's feeding response.